"It's almost expected": rural Australian Aboriginal women's reflections on smoking initiation and maintenance: a qualitative study - Passey Megan E; Gale Jennifer T; Sanson-Fisher Robert W (BMC, 2011)
Abstract Background Despite declining smoking rates among the general Australian population, rates among Indigenous Australians remain high, with 47% of the Indigenous population reporting daily smoking - twice that of other Australians. Among women, smoking rates are highest in younger age groups, with more than half of Aboriginal women smoking during pregnancy. A lack of research focused on understanding the social context of smoking by Aboriginal women in rural Australia limits our ability to reduce these rates. This study aimed to explore the factors contributing to smoking initiation among rural Aboriginal women and girls and the social context within which smoking behaviour occurs. Methods We conducted three focus groups with 14 Aboriginal women and service providers and 22 individual interviews with Aboriginal women from four rural communities to explore their perceptions of the factors contributing to smoking initiation among Aboriginal girls. Results Four inter-related factors were considered important to understanding the social context in which girls start smoking: colonisation and the introduction of tobacco; normalization of smoking within separate Aboriginal social networks; disadvantage and stressful lives; and the importance of maintaining relationships within extended family and community networks. Within this context, young girls use smoking to attain status and as a way of asserting Aboriginal identity and group membership, a way of belonging, not of rebelling. Family and social structures were seen as providing strong support, but limited the capacity of parents to influence children not to smoke. Marginalization was perceived to contribute to limited aspirations and opportunities, leading to pleasure-seeking in the present rather than having goals for the future. Conclusions The results support the importance of addressing contextual factors in any strategies aimed at preventing smoking initiation or supporting cessation among Aboriginal girls and women. It is critical to acknowledge Aboriginal identity and culture as a source of empowerment; and to recognise the role of persistent marginalization in contributing to the high prevalence and initiation of smoking.